Bridge to Persistence: Interactions With Educators as Social Capital for Latina/o Engineering Majors. (July 2018) - Dika, Sandra L.; Martin, Julie P.
This study employs the notion of bridging social capital to investigate the extent to which different forms and quantity of interactions with educators predict intentions to persist in engineering among a sample of Latina/o engineering majors from five public 4-year institutions in the United States. Different forms of capital were effective for women and men on intentions to persist, and learning orientation emerged as the most important predictor of engineering commitment.